Efektifitas Latihan Otot Dasar Panggul dalam Meningkatkan Fungsi Seksual pada Pasien Kanker Ginekologi - Prawesti, Aprilia Dian; Afiyanti, Yati (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effectiveness of pelvic floor muscle exercise in improving sexual function in gynecological cancer patients. The method used in this study uses a systematic review using the procedures recommended in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The author uses several databases, namely PubMed, Cochrane Library, ProQuest, EbscoHost, Sage Journal, Clinical Key Nursing and Google Scholar. The results of this study contained 12 articles consisting of 6 RCTs, 2 Cohort Studies, 1 single arm, 1 Crossectional, 1 clinical report study, 1 mixed method. The conclusion of this study provides data and evidence that pelvic floor muscle exercise not only affects the improvement of sexual function but also affects the improvement of quality of life, changes in anxiety, depression, and pain of gynecological cancer patients. Keywords: Gynecological Cancer, Pelvic Floor Muscle Exercise, Sexual Function